2011
DOI: 10.1002/hbm.21153
|View full text |Cite
|
Sign up to set email alerts
|

Altered default mode network connectivity in alzheimer's disease—A resting functional MRI and bayesian network study

Abstract: A number of functional magnetic resonance imaging (fMRI) studies reported the existence of default mode network (DMN) and its disruption due to the presence of a disease such as Alzheimer’s disease (AD). In this current investigation, firstly, we used the independent component analysis (ICA) technique to confirm the DMN difference between patients with AD and normal control (NC) reported in previous studies. Consistent with previous studies, the decreased resting-state functional connectivity of DMN in AD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(190 citation statements)
references
References 86 publications
11
174
1
4
Order By: Relevance
“…As for the effective connectivity method, there are a variety of methods used to evaluate effective connectivity such as structural equation modeling (SEM) (Mclntosh and GonzalezϋLima, 1994;Schlösser et al, 2003), dynamic causal modeling (DCM) (Friston et al, 2003;Friston et al, 2014), granger causality mapping (GCM) (Goebel et al, 2003;Liao et al, 2010) and Bayesian network (BN) (Wu et al, 2011;Zheng and Rajapakse, 2006). Among these methods, both SEM and DCM are model-driven algorithms which need assumption of priori model, hence, may not suited for resting state fMRI (Heckerman, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the effective connectivity method, there are a variety of methods used to evaluate effective connectivity such as structural equation modeling (SEM) (Mclntosh and GonzalezϋLima, 1994;Schlösser et al, 2003), dynamic causal modeling (DCM) (Friston et al, 2003;Friston et al, 2014), granger causality mapping (GCM) (Goebel et al, 2003;Liao et al, 2010) and Bayesian network (BN) (Wu et al, 2011;Zheng and Rajapakse, 2006). Among these methods, both SEM and DCM are model-driven algorithms which need assumption of priori model, hence, may not suited for resting state fMRI (Heckerman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It can reflect how one brain region influences another and can quantitatively depict the strength of such influence (Friston, 1994). Studies have shown that the altered effective connectivity may serve as a potential biomarker to reveal characteristics of neurological disease such as Alzheimer's disease (Wu et al, 2011) and primary progressive aphasia (Sonty et al, 2007). Similarly, the application of effective connectivity in the depression studies may reflect more pathophysiological characteristics of depression patients from a new perspective and potential use as a biomarker.…”
Section: Introductionmentioning
confidence: 98%
“…Our results are in line with these previous influential studies. A possible integrative view of all the results could be as follows: (1) the higher neuronal activity in the hub regions starts from a dysfunction of cellular inhibition; (2) the consequent disinhibition drives the neural network to an oversynchronization; (3) this oversynchronization is peculiar to the hub regions with a higher amyloid burden; (4) these overactivated regions are prone to degeneration and atrophy; (5) a possible neurophysiological sign of this oversynchronization is the increase in the α 3 /α 2 power ratio we found in typical hub regions [74,75,76,77]. It is of great interest that there is an overlap between the brain regions associated with an increase in the EEG α 3 /α 2 power ratio (hypersynchronization of upper α) in our study and the regions associated with a higher amyloid burden related to memory processes [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these brain regions may connect directly, and share a correlative cortical atrophy [13] caused in AD. In addition, Wu et al suggested that the increased correlation may be due to the connection compensation 239 among brain regions [26], that is some brain regions would enhance their own activity to compensate the decline of synchronism in other regions. Moreover, there were some decreased correlations in AD group, such as MPFC and bilateral hippocampus, left hippocampus and left lateral parietal cortex, left and right inferior temporal cortex as well, which could result from lacking mutually trophic influences of anatomical connectivity between these brain regions [13].…”
Section: B Between-group Correlation Diff Erencesmentioning
confidence: 99%